Perceptual Experience of Visual Motion Activates hMT+ Independently From the Physical Reality: fMRI Insights From the Looming Pinna Figure. (November 2016) - Budnik, U.; Hindi-Attar, C.; Hamburger, K.; Pinna, B.; Hennig, J.; Speck, O.
The human motion processing area, hMT+, has been labeled the critical neural area for processing of real and illusory visual motion in radial 2D patterns. However, the activation in hMT+ during perception of illusory rotation in the looming double-circular Pinna Figure (PF) generated in 3D space has not been observed yet. To do so, an optic-flow like motion of rings (looming) in PF was generated on a computer screen. A psychophysically precise nulling procedure allowed quantifying the individual amount of the perceived illusory rotation in PF (PI) for each participant. The interpolation of the individual illusory motion parameters created a subjectively non-rotating PF and a physically rotating control stimulus of identical rotary strength as the PI. The physically rotating control was a double-circular figure which diverged from PF only in its arrangement of luminance gradients. In a 3-Tesla scanner, participants were presented with a random order of rotating and non-rotating figures (illusory, real, no rotation, and nulled PI). Both types, illusory and real rotation, when equal in perceptual strength for the observer, were found to be processed by hMT+.